Application of thermal therapies and remotely targeted drug delivery systems to treat cancer - Keck, Sarah (Kansas State University, 2023)
Applied cancer research has been heavily focused on novel treatment methods to improve the current standard of care and subsequently ameliorate quality of life. This thesis describes developments in two projects focused on the treatment of aldosterone-producing adenomas and pancreatic ductal adenocarcinoma. The first project characterizes a mouse model for utilization in thermal ablation studies for aldosterone-producing adenomas. A previous study demonstrating tumor response to MRI-targeted microwave ablation in mice had promising results but had challenges associated with an ill-defined mouse model. To address these challenges, a three-part study was executed. The first study tested three different inoculation protocols and determined that injecting 20 million HAC-15 cells suspended in Matrigel resulted in the most homogenous and efficient tumor growth. The second study sampled various intervals following an angiotensin II injection to determine when peak stimulation of aldosterone secretion occurs. The third study utilized tumors of various sizes and recorded aldosterone production to determine if there is correlation between tumor size and aldosterone production. No correlation was detected. From this study, we further characterized a mouse model of primary aldosteronism using the HAC-15 cell line. The defined inoculation protocol resulted in homogenous and efficient growth. The defined aldosterone peak post-angiotensin II injection can be utilized to determine residual tumor function post-treatment. The second project characterized the efficiency and release of encapsulated gemcitabine via triggering the liposomal phase transition temperature (T[subscript m]). Future integration of liposomal chemotherapy and radiofrequency ablation into cancer treatment plans has the potential to reduce systemic effects by initiating targeted release of the anti-cancer agent in the tumor vasculature. Liposomes synthesized with a T[subscript m] of 41°C are remotely loaded with gemcitabine via an ion gradient created with ammonium sulfate. The liposomes were applied to 96-well plates seeded with KPC (mouse) and BXPC-3 (human) pancreatic adenocarcinoma cell lines. Heat was applied via a hot water bath at various temperatures for various amounts of time. MTT reagents were added 24 and 48 hours post-heat treatment. The formazan absorbance was quantified spectrophotometrically and used to demonstrate cell viability. Overall, temperature-triggered release of gemcitabine has had a negative impact on cell viability as shown by the significantly lower viability of the treatment groups as compared to control groups at 24 hours post-heat treatment of both cell lines.
Keywords: Pancreatic cancer; Aldosterone-producing adenoma; Microwave hyperthermia; Thermosensitive liposomes